VALIDITY OF LEARNING TOOLS TO MEASURE CRITICAL THINKING SKILLS OF MADRASAH TSANAWIYAH STUDENTS - Nurul Hidayati; Elly Yustina; Sri Hendra Suryani; Juli Eka Nugraheni (Universitas Lambung Mangkurat, 2021)
The success of a teaching process cannot be separated from the learning tools used, one of the requirements is that the learning tools must be valid. The success of a teaching process is measured by the extent to which students can master the subject matter presented by the teacher. A learning model is needed that can make it easier to develop critical thinking skills so that a truly valid learning tool is obtained to measure the potential and skills that exist in students. Among the learning models that emphasize the process of seeking and finding is the inquiry model. This study aims to prepare in measuring critical thinking skills of Madrasah Tsanawiyah students. The Learning Toolkit has been validated by 3 experts and will then be averaged to find the final score. The values obtained will be entered into the validation criteria table based on the validation criteria table and the results are that the tools made are very valid and can be used in the teaching and learning process because previously the tools made have been revised several times. Keywords: validity, learning tools, critical thinking skills AbstrakKeberhasilan suatu proses pengajaran tidak terlepas dari perangkat pembelajaran yang digunakan, salah satu persyaratan adalah perangkat pembelajaran harus valid. Keberhasilan suatu proses pengajaran diukur dari sejauh mana siswa dapat menguasai materi pelajaran yang disampaikan guru. Diperlukan suatu model pembelajaran yang dapat memudahkan dalam mengembangkan perangkat keterampilan berpikir kritis sehingga didapatkan suatu perangkat pembelajaran yang benar-benar valid untuk mengukur potensi dan keterampilan yang ada pada diri siswa. Diantara model pembelajaran yang menekankan kepada proses mencari dan menemukan adalah model inkuiri. Penelitian ini bertujuan untuk mempersiapkan dalam mengukur keterampilan berpikir kritis siswa Madrasasah Tsanawiyah. Perangkat Pembelajaran sudah divalidasi oleh 3 orang ahli kemudian akan dirata-ratakan untuk mencari nilai akhir. Nilai yang didapat akan dimasukkan ke dalam tabel kriteria validasi diberdasarkan tabel kriteria validasi dan hasilnya perangkat yang dibuat termasuk sangat valid dan dapat digunakan dalam proses belajar mengajar karena sebelumnya perangkat yang dibuat sudah dilakukan beberapa kali revisi. Kata kunci: kevalidan, perangkat pembelajaran, keterampilan berpikir kritis